Status Sosial Unsur Penokohan Pada Cerita Pendek â€œSang Guru Jukiâ€ Karya Ahmad Tohari - Ardhian Nurhadi; Nova Daniar Adriyanti (Jurusan Tadris Bahasa Indonesia, 2020)
This study aims to examine and determine the function of social status and role of the behaviour and character of figures in the community system. The data source in this study is a short story entitled